Characteristics of anatomical difficulty for cryoballoon ablation: insights from CT. Issue 1 (6th January 2022) - Hayashi, Takahiro; Murakami, Masato; Saito, Shigeru; Iwasaki, Kiyotaka
Abstract : Background: The limited availability of balloon sizes for cryoballoon leads to anatomical limitations for pulmonary vein (PV) isolation. We conducted a comprehensive systematic analysis on procedural success rate, atrial fibrillation (AF) recurrence rate and complications of cryoballoon ablation in association with the anatomy of the left atrium and PV based on preprocedural CT to gain insights into proper treatments of patients with AF using cryoballoon. Method: A systematic search of literature databases, including PubMed, Web of Science and Cochrane Library, from the inception of each database through February 2021 was conducted. Search keywords included 'atrial fibrillation', 'cryoballoon ablation' and 'anatomy'. Results: Overall, 243 articles were identified. After screening, 16 articles comprising 1396 patients were included (3, 5 and 8 for acute success, AF recurrence and complications, respectively). Regarding acute success and AF recurrences, thinner width of the left lateral ridge, higher PV ovality, PV ostium-bifurcation distance, shorter distance from the non-coronary cusp to inferior PVs, shallower angle of right PVs against the atrial septum and larger right superior PV (RSPV) were associated with poor outcomes. Regarding complications, shorter distance between the RSPV ostium and the right phrenic nerve, larger RSPV-left atrium angle, larger RSPV area and smaller right carina width were associated with incidences of phrenic nerve injury. Conclusion: This study elucidated several key anatomical features of PVs possibly affecting acute success, AF recurrence and complications in patients with AF using cryoballoon ablation. CT analysis has helped to describe benefits and anatomical limitations for cryoballoon ablation.